2014
DOI: 10.1111/bjhp.12102
|View full text |Cite
|
Sign up to set email alerts
|

From lists of behaviour change techniques (BCTs) to structured hierarchies: Comparison of two methods of developing a hierarchy of BCTs

Abstract: Objectives. Behaviour change technique (BCT) Taxonomy v1 is a hierarchically grouped, consensus-based taxonomy of 93 BCTs for reporting intervention content. To enhance the use and understanding of BCTs, the aims of the present study were to (1) quantitatively examine the 'bottom-up' hierarchical structure of Taxonomy v1, (2) identify whether BCTs can be reliably mapped to theoretical domains using a 'top-down' theoretically driven approach, and (3) identify any overlap between the 'bottom-up' and 'top-down' g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
351
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 282 publications
(362 citation statements)
references
References 66 publications
7
351
0
Order By: Relevance
“…Motivation was an important mediator of the influence of Capability which turned out to be the key driver of MVPA for healthy adults, and so both constructs should be promising targets for an intervention aimed at encouraging or maintaining physical activity. Recent work has begun to show how TDF domains can be linked to individual BCTs (Cane et al, 2015), and identified those BCTs that are included in effective interventions for inactive adults (Howlett et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Motivation was an important mediator of the influence of Capability which turned out to be the key driver of MVPA for healthy adults, and so both constructs should be promising targets for an intervention aimed at encouraging or maintaining physical activity. Recent work has begun to show how TDF domains can be linked to individual BCTs (Cane et al, 2015), and identified those BCTs that are included in effective interventions for inactive adults (Howlett et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…One benefit of the theoretical focus of this research is that specific behavioural determinants can be linked to change strategies and indeed evidence suggests that TDF-based interviews may encourage respondents to identify barriers that they would not otherwise disclose [28]. Cane et al have aligned behaviour change techniques mapped to TDF behavioural determinants as an aid to characterising and designing behaviour change interventions [29]. For example, while information provision via education and training may be relevant to change knowledge and skills, altering beliefs of consequences may require persuasive communication and monitoring the consequences of one's own behaviour.…”
Section: A Dexteritymentioning
confidence: 99%
“…73 However, it is not only the content and form of the taxonomy that drives reliable and valid application of BCT labels/definitions but also the extent to which the user has been trained to use the taxonomy. Identifying (coding) BCTs involves a deductive process of categorising qualitative information (e.g.…”
Section: Introductionmentioning
confidence: 99%